Age structure, growth performance and composition of native and invasive Salicaceae in Patagonia - Thomas, Lisa K. (Plant Ecology, 2014)
In northern Patagonia, riparian ecosystems are highly modified due to alien plant invasions. The establishment of non-native willows and poplars has unknown effects for Salix humboldtiana, the only native floodplain tree species in this region. To clarify establishment processes and to assess whether interspecific competition among the Salicaceae taxa may occur and therefore whether the native species can coexist in the long term, we analysed age structure and growth performances of the dominant four taxa within mixed adult forest stands along the Río Negro, Argentina. Low mean ages of <15 years for all four taxa within 20 stands could be detected and suggest frequent and severe disturbances resulting in the removal of existing vegetation and subsequent creation of sites for establishment. Trees of the same stand showed the same age structure indicating joint establishment events with all taxa involved. A significant better growth performance (basal area, crown diameter) could be proved for the invasive willows. Considering the upper and middle river separately in a total of 88 studied plots, S. humboldtiana was more frequent at the middle river stretch, while invasive willows showed an opposing pattern suggesting a downstream directed invasion process. The results showed that competition pressure in mature mixed stands could affect S. humboldtiana. However, these stands are usually removed by river dynamics creating new sediment bars and islands. These processes enable S. humboldtiana seeds to germinate frequently which may compensate for its inferior growth performance and potential impacts by the invasive willows and poplars.